INTEGRATION OF ISLAM AND HEALTH SCIENCE: INTEGRASI ISLAM DAN ILMU KESEHATAN - Opi Irawansah (UPT PPM Sekolah Tinggi Ilmu Kesehatan Al Irsyad Al Islamiyyah Cilacap, 2021)
Health science is a branch of science that is very important in human life. Currently, health science has been studied in various perspectives, one of which is the Islamic perspective. Basically, health science and Islam support and strengthen each other. There are lots of arguments and evidence that Islam is very concerned about health. Likewise, health science has a lot to do with Islam. Many cases in health science require legal provisions according to Islamic guidance. However, there are many facts that show that Muslims still separate Islam and health sciences. Many religious scholars do not pay attention to health problems related to Islam. Likewise, health experts do not pay attention to Islamic laws related to health sciences. This fact makes a gap between Islamic teachings and health sciences in the lives of Muslims. This study aims to explain the form of integration between Islam and health science which has so far been deemed unrelated both in theory and practice. This study will analyze the form of integration between Islam and health science. This research method uses literature studies by collecting library data, reading and taking notes, and managing research materials. The results of this study indicate that the form of understanding that separates Islam from health sciences can be divided into three parts. This study also shows that there are three forms that describe the relationship between Islam and health sciences which are dialogical and integrative, they are, 1) Semipermeable, 2) intersubjective subjectivity, and 3) Creative Imagination. Keywords: Integration, Islam, Health Sciences